2019
DOI: 10.1093/ej/uez063
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Preferences and Ethnicity: Experimental Evidence from Bangladesh

Abstract: We investigate whether aversion to competing against members of the ethnically dominant group could be a contributing factor to the persistent disadvantageous socioeconomic position of ethnic minorities. We conducted a lab-in-the-field experiment in rural Bangladesh, randomly assigning participants into groups with different ethnic composition. We find that the ethnic minority group (Santal) are less likely to compete in groups where they are a numerical minority than when all competitors are co-ethnic, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Almås et al (2016b) find that gender differences in competitiveness arise between boys and girls from families with a high socioeconomic status only, and not between those who are from families with a low socioeconomic status. Siddique and Vlassopoulos (2019) report that people from an ethnic minority group are more likely to compete when their competitors are all co-ethnic than when their competitors are predominantly from the majority group.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Almås et al (2016b) find that gender differences in competitiveness arise between boys and girls from families with a high socioeconomic status only, and not between those who are from families with a low socioeconomic status. Siddique and Vlassopoulos (2019) report that people from an ethnic minority group are more likely to compete when their competitors are all co-ethnic than when their competitors are predominantly from the majority group.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The first of these possibilities is our operational definition of norm generalization, while the last possibility represents a form of compensating for past inequalities. Strikingly, recent research has shown that, when adults from different ethnicities play experimental games, participants from the underprivileged ethnic group also play the game in a way that perpetuates their underprivileged status (Siddique & Vlassopoulos, 2020).…”
Section: Hypothesesmentioning
confidence: 99%
“…In effect, when considering how to distribute, farmers and land owners simply give up, defer to the norm, and get on with the business of growing corn (Young & Burke, 2001). If the local norm is inequitable, however, it can create and perpetuate status differentials that might spill over and affect other types of exchange in other social domains (Bowles, 2009;Henrich & Boyd, 2008;Holm, 2000;Siddique & Vlassopoulos, 2020). To the extent that this happens, the parties involved generalize the norm beyond the original problem, namely how to distribute the gains from sharecropping, to other types of exchange, for example who defers to whom when a farmer and land owner meet in the street?…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have also examined differences in overconfidence between East Asian and Western populations with mixed results (e.g., Kitayama, Markus, Matsumoto, & Norasakkunkit, 1997;Muthukrishna, Henrich, Toyokawa, Hamamura, Kameda, & Heine, 2018;Yates, Lee, & Bush, 1997). Lastly, in the competitive-preferences literature, Carlsson, Lampia, Martinssona, & Yangb (2020) replicate the main findings of NV 2007 using adult Han Chinese in a lab-in-thefield experiment; and Siddique & Vlassopoulos (2020) find that, despite no differences in objective performance, members of a socioeconomically disadvantaged ethnic minority in Bangladesh are more willing to compete when fewer members of the advantaged ethnic majority are in the group of potential competitors.…”
Section: Introductionmentioning
confidence: 98%